Compensatory Responses During Slip-Induced Perturbation in Patients With Knee Osteoarthritis Compared With Healthy Older Adults: An Increased Risk of Falls? - Ren, Xiping; Lutter, Christoph; Kebbach, Maeruan; Bruhn, Sven; Yang, Qining; Bader, Rainer; Tischer, Thomas (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Functional impairment of the knee joint affected by osteoarthritis and loss of muscle strength leads to a significant increase in the number of falls. Nevertheless, little is known about strategies for coping with gait perturbations in patients with knee osteoarthritis (KOA). Thus, this study aimed to examine the compensatory strategies of patients with KOA in response to a backward slip perturbation compared with healthy older adults. Methods: An automated perturbation program was developed by using D-Flow software based on the Gait Real-time Analysis Interactive Lab, and an induced backward slip perturbation was implemented on 9 patients with severe KOA (68.89 ± 3.59 years) and 15 age-matched healthy older adults (68.33 ± 3.29 years). Step length, gait speed, range of motion, vertical ground reaction forces, lower extremity joint angles, and joint moments were computed and analyzed. Results: Compared with older adults, patients with KOA had significantly lower step length, gait speed, and vertical ground reaction forces in both normal walking and the first recovery step following backward slip perturbations. Inadequate flexion and extension of joint angles and insufficient generation of joint moments predispose patients with KOA to fall. Hip extension angle and flexion moment, knee range of motion, and vertical ground reaction forces are key monitoring variables. Conclusion: The risk of falls for patients with KOA in response to backward slip perturbations is higher. Patients with KOA should focus not only on quadriceps muscle strength related to knee range of motion but also on improving hip extensor strength and activation through specific exercises. Targeted resistance training and perturbation-based gait training could be better options.